Obesity (Los Angeles: National Health Video)
(Producer) This video cover the definition of obesity, cause obesity, physical activity, surgery, diet, problem associated with obesity and child abesity. It recommended physical activity is a key factor in weight management.
Videocassettes is available at Koleksi Media, Perpustakaan PPUKM
Keywords: Obesity -- therapy -- videocassettes